The Effects of Mindfulness-Based Cognitive Therapy on Affective Memory Recall Dynamics in Depression: A Mechanistic Model of Rumination - Van Vugt, Marieke K.; Hitchcock, Peter; Shahar, Ben; Britton, Willoughby (Frontiers in Human Neuroscience, 2012)
Objectives: Converging research suggests that mindfulness training exerts its therapeutic effects on depression by reducing rumination. Theoretically, rumination is a multifaceted construct that aggregates multiple neurocognitive aspects of depression, including poor executive control, negative and overgeneral memory bias, and persistence or stickiness of negative mind states. Current measures of rumination, most often self-reports, do not capture these different aspects of ruminative tendencies, and therefore are limited in providing detailed information about the mechanisms of mindfulness. Methods: We developed new insights into the potential mechanisms of rumination, based on three model-based metrics of free recall dynamics. These three measures reflect the patterns of memory retrieval of valenced information: The probability of first recall (Pstart) which represents initial affective bias, the probability of staying with the same valence category rather than switching, which indicates strength of positive or negative association networks (Pstay); and probability of stopping (Pstop) or ending recall within a given valence, which indicates “drift” persistence or stickiness of a mind state. We then investigated the effects of MBCT (N=29) vs wait-list control (N=23) on these recall dynamics in a Randomized Controlled Trial (RCT) in individuals with recurrent depression. Participants completed a standard laboratory stressor, the Trier Social Stress Test (TSST), to induce negative mood and activate ruminative tendencies. Then, participants completed a free recall task consisting of three word lists. This assessment was conducted both before and after treatment or wait-list. Results: While MBCT participant’s Pstart remained relatively stable, controls showed multiple indications of depression-related deterioration towards more negative and less positive bias. Following the intervention, MBCT participants decreased in their tendency to sustain trains of negative words